Using the International Phonetic Alphabet in Teaching English Oral Production and Reception to Algerian Learners as a Potentially Efficient Solution to the Sound Spelling Incoherence - Beghoul, Youcef (Journal of Human Sciences, 2017)
This paper deals with using the phonetic transcript in teaching English oral production and listening comprehension to Algerian learners of English. It is assumed to be a practical solution to the problems caused by English spelling inconsistency. Transcription has been used, though maligned by many,to clear spelling ambiguity, but applied only to segments and stress in isolated words inthe subject of phonetics. It has seldom been a tool in teaching the oral productive and receptive skills. An analysis of the use of this means as part of teaching English oral skill in the course books used in the intermediate and secondary schools as well as how it is used at university in the subject of oral skill reveals that it is used in a rather limited way, inadequately and with many shortcomings. Some practical suggestions are made to use the phonetic transcript in a much more practical way covering both the productive and the receptive oral skills.